2012
DOI: 10.1016/j.ajhg.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent De Novo Mutations in PACS1 Cause Defective Cranial-Neural-Crest Migration and Define a Recognizable Intellectual-Disability Syndrome

Abstract: We studied two unrelated boys with intellectual disability (ID) and a striking facial resemblance suggestive of a hitherto unappreciated syndrome. Exome sequencing in both families identified identical de novo mutations in PACS1, suggestive of causality. To support these genetic findings and to understand the pathomechanism of the mutation, we studied the protein in vitro and in vivo. Altered PACS1 forms cytoplasmic aggregates in vitro with concomitant increased protein stability and shows impaired binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
138
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 16 publications
8
138
0
1
Order By: Relevance
“…Together, the recurrence of this particular mutation and the absence of mutations at other positions in the gene, strengthens our previous proposal of a dominant-negative or a gain-of-function effect at the protein level [Schuurs-Hoeijmakers et al, 2012]. The mutation is located in the furin cargo binding domain, directly adjacent to a CK2-binding motif that is essential for PACS1 autoregulation and might affect the auto regulatory property of the protein as well as interaction with cargo, or adaptor binding.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Together, the recurrence of this particular mutation and the absence of mutations at other positions in the gene, strengthens our previous proposal of a dominant-negative or a gain-of-function effect at the protein level [Schuurs-Hoeijmakers et al, 2012]. The mutation is located in the furin cargo binding domain, directly adjacent to a CK2-binding motif that is essential for PACS1 autoregulation and might affect the auto regulatory property of the protein as well as interaction with cargo, or adaptor binding.…”
Section: Discussionsupporting
confidence: 54%
“…We have previously described two unrelated boys with a strikingly similar facial appearance, moderate intellectual disability, and cryptorchidism who carry an identical de novo mutation in PACS1 (NM_0180026.2, OMIM 615009: Mental Retardation, Autosomal Dominant 17) [Schuurs-Hoeijmakers et al, 2012]. This finding of an identical de novo c.607C>T mutation in two individuals that shared strikingly similar clinical findings, suggested that mutations in PACS1 define a recognizable syndromic form of intellectual disability.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…To establish the pathogenicity of mutations in such candidate ID genes, it is essential to identify additional individuals with an overlapping phenotype and a mutation in the same gene. [3][4][5] With increasing availability of WES in routine diagnostics 6 as well as technological advances facilitating targeted resequencing of candidate ID genes in larger cohorts of samples, 7 chances of finding such additional individuals are increasing. Furthermore, supporting evidence and insights into underlying mechanisms can be obtained from functional studies in cell or animal models.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Similarly, largescale WES studies of individuals affected by ID/DD have recently leveraged this phenomenon as supporting evidence of the involvement of a gene in disease. 7,8 This spatial clustering of de novo mutations (DNMs) is typical for missense mutations in genes without clear, or limited numbers of, truncating mutations subsequently degraded by nonsense-mediated mRNA decay, suggesting that these clustered mutations act through a different mechanism than haploinsufficiency (HI).…”
mentioning
confidence: 99%